Evaluation of the PhunkyFoods intervention on food literacy and cooking skills of children aged 7–9 years: a cluster randomised controlled trial in Yorkshire Primary Schools UK - Karen L. Vaughan; Janet E. Cade; Marion M. Hetherington; Jennie E. Cockroft; Mirjam M. Heinen; Holly Rippin; Charlotte E. L. Evans (Trials, 2022)
Abstract Background Childhood obesity rates more than double during primary school in England. Acquiring competent cooking skills is a key part of children’s education that can lead to improved knowledge of a healthy lifestyle and dietary behaviours. Evaluation of the impact of ‘PhunkyFoods’, a school-based food and nutrition education programme, will assess food literacy, cooking skills and dietary behaviour in primary-school children. Methods A cluster randomised controlled trial will be undertaken in 28 primary schools in North Yorkshire, UK, including a total population of children aged 7–9 years (n = 420). The trial has two arms: (a) the intervention group receiving PhunkyFoods programme (n = 210) and (b) the wait-list control group receiving the usual school curriculum (n = 210). The intervention ‘PhunkyFoods’ will be delivered by Purely Nutrition Ltd. The participating school staff are supported with training, policy development and access to resources to improve the delivery of nutrition education. Children participate through whole school assemblies, classroom activities, and after-school clubs about food preparation, cooking healthy meals and healthy living. Schools, parents and children have access to healthy meal recipes through the PhunkyFoods website. The primary outcomes are differences in food literacy and cooking skills scores between control and intervention arms after 12 months of the intervention and adjusted for baseline values. The secondary outcome is differences in fruit and vegetable intake between the arms after 12 months (adjusted for baseline). Treatment effects will be examined using mixed ANOVA and regression analysis. Primary analyses will adjust for baseline food literacy and cooking skills scores and secondary analysis will adjust for pre-specified baseline school and child level covariates. Discussion The PhunkyFoods programme is a flexible menu of options for schools to choose from, making this a highly complex intervention. Following Medical Research Council guidance, research perspectives will focus on effectiveness and theory-based approaches: to what extent the intervention produces the intended outcomes in real-world settings and what works in which circumstances. Trial registration ISRCTN ISRCTN68114155 . Prospectively registered on 22 October 2021